2006
DOI: 10.3200/psfl.50.3.13-20
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of System-of-Care Participation on School Functioning: Exploring Caregiver and Teacher Perspectives

Abstract: There is some evidence that systems of care are associated with improved outcomes for the children and youths who participate; however, little research has been conducted on how these approaches affect student functioning in school. In this study, the authors explored the relationship between participation in the Dawn Project system of care and changes in school functioning over time. The authors gathered, analyzed, and compared teacher and caregiver perspectives of changes that occurred in students' school fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…While parents of children with disabilities are strong supporters of school-based collaboration, many continue to report negative interactions with educators that have adversely affected the collaborative processes (Anderson, Meyer, and Somers 2006;Bernheimer and Weisner 2007;Kasahara and Turnbull 2005;Starr et al 2006;Wilgosh and Scorgie 2006).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…While parents of children with disabilities are strong supporters of school-based collaboration, many continue to report negative interactions with educators that have adversely affected the collaborative processes (Anderson, Meyer, and Somers 2006;Bernheimer and Weisner 2007;Kasahara and Turnbull 2005;Starr et al 2006;Wilgosh and Scorgie 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In a qualitative study of parents of children with disabilities, Kearney and Griffin concluded that the greatest difficulties parents faced 'derived from their dealings with other people's frequent messages of negativity and hopelessness ' (2001, 586). Research reports that many professionals feel inadequately prepared to serve families of children with special needs (Anderson, Meyer, and Somers 2006;Deck et al 1999). To address this concern, Bernheimer and Weisner (2007) recommended that teacher preparation programmes better prepare educators to work collaboratively with parents, specifically targeting attitudes of professionals toward parents.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…having their views disregarded by professionals, being asked to approve and sign programme plans without prior input, being forced to focus primarily on child deficits, lack of sufficient time for meetings, and goals that are jointly negotiated but not achieved (Anderson, Meyer, and Somers 2006;Ankeny, Wilkins, and Spain 2009;Beauregard 2011;Fish 2006;Kalyanpur, Harry, and Skrtic 2000;Obiakor 2007;Valle and Aponte 2002). Parents are also aware that some teachers hold lower expectations for their children, and that their children experience social marginalisation in the school environment, even when placed in 'inclusive' settings (Chmiliar 2009;Leyser and Kirk 2004;McMahon et al 2008;Smoot 2004).…”
mentioning
confidence: 99%